A preliminary account of investigations into the False Bay sublittoral by the use of a diving helmet - Jackson, P B N (Peter Brian Neville), 1923- (Department of Biological Sciences, 2024)
A great deal of work has been done on the ecology of the intertidal some of South African by the Zoology Department of the University of Cape Town under the direction of Professor T.A. Stephenon. As a result of this a number of valuable papers have been published dealing with the plants and animals of the zone, their ecology, lateral and vertical distribution and so on. Stephenon has, in three papers (1939, 1944,1947), dealt with general results and conclusions drawn from this survey. This work dealt entirely with the biotic between tidelevels, i.e., from the sublittoral fringe upward. it did not take into account the sublittoral, that part of the shallow coast which is perpetually submerged at all tides.